2010
DOI: 10.4314/njbas.v18i1.56841
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Promotes Apoptosis and Expression of Pro-Inflammatory Mediators in Alternatively Activated Macrophages

Abstract: ABSTRACT:Accumulation of lipid within non-adipose tissues can induce inflammation by promoting macrophage infiltration and activation. Oxidized lipoproteins (oxLDL) have been known to induce cellular dysfunction in resident macrophages through pro-inflammatory and pro-apoptotic properties. However research into the pro-inflammatory and pro-apoptotic effects of oxLDL in alternatively activated (M2) macrophages has been relatively sparse. In this study, the proinflammatory and pro-apoptotic effects of oxLDL (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Consequently, oxidized LDL induces inflammatory responses in blood vessels that lead to atherogenesis [ 25 ]. Recent studies suggest that increased lipid oxidation is also associated with T2D and obesity via inflammation [ 33 , 34 ]. In our study, concentrations of LDL and triglycerides were significantly elevated in the FTO carrier group compared with the control group (LDL: 123.6 ± 31.69 vs. 121 ± 31.82 mg/dL, p < 0.05; triglycerides: 139.3 ± 72.51 vs. 132.21 ± 67.67 mg/dL, p < 0.05; S1 Fig ), whereas HDL levels were similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, oxidized LDL induces inflammatory responses in blood vessels that lead to atherogenesis [ 25 ]. Recent studies suggest that increased lipid oxidation is also associated with T2D and obesity via inflammation [ 33 , 34 ]. In our study, concentrations of LDL and triglycerides were significantly elevated in the FTO carrier group compared with the control group (LDL: 123.6 ± 31.69 vs. 121 ± 31.82 mg/dL, p < 0.05; triglycerides: 139.3 ± 72.51 vs. 132.21 ± 67.67 mg/dL, p < 0.05; S1 Fig ), whereas HDL levels were similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is necessary to find more effective methods to stimulate migration of bmMSCs. It has been reported that ox-LDL can induce production of inflammatory molecules (MCP-1, IL-6, and adhesive molecules), and subsequently promote migration of macrophages and endothelial cells [2729]. …”
Section: Discussionmentioning
confidence: 99%